Nino & Sonia: The Dark Horse Heroes of Criminal Justice on the Roberts Court - Shahrzad Daneshvar; Brooke Clason Smith (Washington University Journal of Law & Policy, 2017)
This Article traces the voting records of the Supreme Court justices in criminal cases during the Roberts court to determine whether a justice’s perceived liberal or conservative ideology can help predict whether a justice’s vote would be sympathetic toward a criminal defendant. Daneshvar and Smith particularly analyzed whether the justices voted consistently with their perceived ideology, where liberal justices are believed to be more sympathetic toward criminal defendants and conservative justices more unsympathetic. By analyzing the voting patterns of the court from 2009 through the 2014 term, Daneshvar and Smith find that in criminal cases Justice Sonia Sotomayor appears to be the most liberal-leaning, while the late Justice Antonin Scalia’s originalist interpretation on constitutional matters made him the justice least consistent to side with his perceived ideology.
Keywords: Supreme Court; Ideology; Criminal; Judicial-behavior; Roberts Court; Sotomayor; Scalia; Procedure; Voting Record